Measurement uncertainty evaluation by kurtosis method at micrometer calibration - Zakharov, I. P.; Botsiura, O. A.; Tsybina, I.; Zakharov, O. ("Софттрейд", 2020)
The procedure for measurement uncertainty evaluation at micrometer calibration by the kurtosis method is considered. The measurement model as the deviation of the micrometer readings from the length of the reference gage block is recorded. The measurement model takes into account the corrections for the micrometer resolution to be calibrated, lack of flatness and departure from parallelism of its measuring faces, as well as for the temperature difference between the gage block and the calibrated micrometer. The input values and their standard uncertainties are estimated. The calculation of the combined standard uncertainty and expanded uncertainty is carried out taking into account the kurtosis of the input quantities. The report presents an uncertainty budget, which can serve as a basis for creating a software tool that facilitates calculations. The proposed procedure was validated by the Monte Carlo method, which showed that it is are adequate for an intended use.
Keywords: measurement uncertainty; micrometer; calibration; kurtosis method